Workplace Diversity and Inclusion as Drivers of Sustainable Business Practices in Building Sustainable Business and Corporate Social Responsibility: Study of Impact and Implementation Strategy - Kamaludin, Ahmad; Pratiwi, Vina Andita (Papanda Publisher, 2025)
Objective: This research aims to reveal the impact, trends and implementation strategies in the field. Bibliometric analysis uses VOSviewer to visualize influential authors, frequently cited works, thematic groups, and keyword distribution. Additionally, the qualitative investigation explores real-world implementation strategies used by organizations for sustainable business practices and CSR initiatives. Methodology/approach: This research uses a combination of bibliometric analysis and qualitative exploration to comprehensively analyze sustainable business practices and corporate social responsibility (CSR).Analysis was carried out using Bibliometric Analysis, Qualitative Exploration, Data Analysis, Identification of Influential Authors. Results/findings: The findings of this research reveal that the results collectively increase understanding of how businesses can effectively integrate sustainability and social responsibility, emphasizing the need for strategic analysis, practical implementation and consideration of the implications and challenges in the practical areas of sustainable business and CSR. Limitations: One of the limitations of this research is that it focuses on analyzing existing literature and does not involve original empirical research to validate the findings due to the broad topic coverage, several specific areas in business practice sustainability and CSR have not been explored in depth. Contribution: This research contributes to the analysis of sustainable business practices & corporate social responsibility (CSR) through a mixture of bibliometric analysis and qualitative exploration. Revealing impacts, trends and strategies for implementing sustainable business practices and CSR initiatives in the field, offering practical insights for organizations. Acknowledging influential authors and important works that have contributed significantly to the understanding of sustainability and CSR thereby shaping academic discourse in this domain. Revealing general implementation strategies such as supply chain optimization, stakeholder engagement, efficiency of resources used by organizations, providing practical approaches for businesses looking to integrate sustainability and CSR into their operations.